Application of a myoelectric elbow flexion assist orthosis in adult traumatic brachial plexus injury: patient perspectives. Issue 6 (December 2021) - Webber, Christina M.; Egginton, Jason S.; Shin, Alexander Y.; Kaufman, Kenton R.
Abstract : Background: Individuals with brachial plexus injuries (BPIs) can be prescribed assistive devices, including myoelectric elbow orthoses (MEOs), for rehabilitation or functional use after failed treatment for elbow flexion restoration. Although recent case studies indicate potential for clinical improvements after using an MEO after BPI, the patients' perspectives on such use are still unknown. Objective: To explore patient perspectives on the use of an MEO after surgical treatment for a traumatic BPI. Study design: Qualitative using both a focus group and semistructured interviews. Methods: Patients with BPI that used an MEO were recruited. Five patients participated in an in-person focus group, whereas three patients participated in individual phone interviews. Themes that emerged from the focus group were compared against those that emerged from the personal interviews. Results: Feedback was grouped into three themes: device usage, hardware performance, and device design. Within each theme, positive elements, areas for improvement, and additional considerations emerged. Patients indicated a positive attitude toward using an MEO as a rehabilitation tool. They desired a streamlined, stronger device to support them and assist during activities of daily living. Conclusions: For patients with BPI, a well-designed MEO that meets their needs could assist with rehabilitation and increase independence in daily activities. Continued patient engagement in the evaluation and development of both medical devices and treatment plans offers the best opportunity for improved outcomes that are important to the patient.